Applying blockchain for primary financial market: A survey. Issue 2 (24th September 2021) - Liu, Ji; Xu, Zheng; Li, Ruiqiang; Zhao, Hang; Jiang, Hongbo; Yao, Jinhui; Yuan, Dong; Chen, Shiping
Abstract: In financial market, especially primary market, it is very costly and difficult to make a deal due to discovery difficulty, information asymmetry, lack of trust, complicated trading process and low liquidity. Blockchain is an innovative technology enabling new business models of distributed data storage, point‐to‐point transaction and decentralized autonomous organizations via consensus. The unique features of blockchain, 'decentralization, highly transparent, enhanced security and immutability of information', make it a good solution candidate to meet the needs of private equity exchange. This article focuses on analysing the technical basis of the blockchain financial model and the typical application scenarios of the blockchain in the financial market. It discusses the importance of applying key blockchain technology to the financial market, especially in the primary market. Research has found that the development of blockchain technology, especially the maturity of stabilized token technology, makes it possible for blockchain to become a supporting technology to support the next generation of infrastructure in the future financial market. At present, blockchain technology has been concentrated in the issuance, registration, clearing, settlement and derivatives management of private equity and other over‐the‐counter securities. The use of blockchain to build a decentralized primary market has not received enough attention in research and practice, and the use of blockchain technology to establish a primary market with diverse distribution methods is still in its infancy. On this basis, this article further analyses the current problems and the possibility of solving these problems in the application of blockchain in the primary market and points out several interesting directions for future research in this field.